„Amadeusz”. Miloš Forman i Peter Shaffer - Choczaj, Małgorzata (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The study is devoted to Miloš Forman’s film, a story about Mozart’s life, taken from Peter Shaffer’s drama. The author proposes a detailed analysis of Forman’s film as an autonomous work in the production of which the film was a medium. The film was an effect of collaboration between the author of the play and the director. The effect of the work is a film which is an example of a close connection of the form and the content – harmony between picture and music, which becomes almost one of the main characters. Individual compositions of Mozart form a network of motives closely connected with the visual aspect and make its sense deeper according to several rules of showing music as a part of the film medium, such as musical motives, explaining the music by the composer or music which uses media. Connecting the music and the aesthetics of the film make Amadeus a harmonious audio-visual performance.
Amadeus. Miloš Forman and Peter Shaffer